ANALYSIS OF CANOLA (RAPESEED) PRODUCTION COST AND INCOME IN CONTEXT OF OILSEEDS PRODUCTION SUPPORT POLICIES: A CASE STUDY FROM TRAKYA REGION OF TURKEY - Yılmaz, Hasan; Avkiran, Buse (Economics of Agriculture, 2020)
The study aimed to analysis the cost and income of canola production in the context of support policies to oilseeds production in the Trakya region of Turkey. In this study, the average production costs of canola were calculated as 600.13 US ha-1. Gross profit and net profit excluding support payments were found as 515.98 and 310.32 US ha-1, respectively. It was determined that the gross profit and net profit including support payments were found to be 921.37 and 715.72 US ha-1. It was calculated that the share of supports is 44% in gross and 56.64% in net profits. The results indicated that the supports of diesel oil, fertilizer, certified seed usage and premium support have important increasing effects on farmer income and decreasing costs in canola production. As a result, it can be said that with the support policies applied in canola production, important increases have occurred in canola cultivation areas and production in Turkey. In order to have an efficient oilseed support policy, farmers extension service should develop various programs regarding sustainable canola production practices to educate farmers.